2014
DOI: 10.3390/pathogens3030596
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Mechanisms of Pseudomonas aeruginosa and Escherichia coli Biofilm Formation

Abstract: Pseudomonas aeruginosa and Escherichia coli are the most prevalent Gram-negative biofilm forming medical device associated pathogens, particularly with respect to catheter associated urinary tract infections. In a similar manner to Gram-positive bacteria, Gram-negative biofilm formation is fundamentally determined by a series of steps outlined more fully in this review, namely adhesion, cellular aggregation, and the production of an extracellular polymeric matrix. More specifically this review will explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
108
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 228 publications
(265 reference statements)
0
108
0
3
Order By: Relevance
“…Thus, it is possible that this structural support might have been reinforced by DNA from lysed cells of strain MG1655[pSB536] thereby increasing the protective effect of the biofilm matrix. Additionally, extracellular polymers of strain MG1655[pSB536], such as curli fibers or cellulose (Laverty et al 2014;Serra and Hengge 2014), might have also interacted with those of strain PAO1. Earlier studies have shown that P. aeruginosa can facilitate biofilm formation of E. coli in a flow-cell capillary (Klayman et al 2009) and on silicone coupons in synthetic urine medium (Cerqueira et al 2013) indicating potential specific interactions between these two bacterial species during biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that this structural support might have been reinforced by DNA from lysed cells of strain MG1655[pSB536] thereby increasing the protective effect of the biofilm matrix. Additionally, extracellular polymers of strain MG1655[pSB536], such as curli fibers or cellulose (Laverty et al 2014;Serra and Hengge 2014), might have also interacted with those of strain PAO1. Earlier studies have shown that P. aeruginosa can facilitate biofilm formation of E. coli in a flow-cell capillary (Klayman et al 2009) and on silicone coupons in synthetic urine medium (Cerqueira et al 2013) indicating potential specific interactions between these two bacterial species during biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation is induced by genotypic and phenotypic changes of the planktonic microorganisms which lead to an ensuing multilayered cell cluster structure coated by an external polysaccharide matrix composed of polysaccharides, proteins, and extracellular DNA (8). P. aeruginosa, once organized in a biofilm structure, becomes more resistant to antibiotic agents and immune system clearance and thus requires a more elaborate strategy for successful treatment of associated infections (9).…”
mentioning
confidence: 99%
“…Examples of social interactions include swarming motility, biofilm formation and quorum sensing; these are well studied in bacteria [1][2][3][4][5] and in the free-living amoeba Dictyostelium discoideum [6], but are not widely recognised in parasites.…”
mentioning
confidence: 99%